Specific and common therapeutic factors in psychodynamic psychotherapy for children and adolescents: an overview - Sammer-Schreckenthaler, Sabine; Lagetto, Gloria; Unterrainer, Human-Friedrich; Gelo, Omar C. G. (Frontiers in Psychology, 2025)
The effectiveness of psychodynamic psychotherapy for children and adolescents (PPCA) has been increasingly demonstrated by a growing number of meta-analyses. However, very little is still known about the therapeutic factors responsible for this effectiveness. On the one hand, some authors have suggested that PPCA works because of specific therapeutic factors. On the other hand, it has been suggested that the effectiveness of PPCA may be due to factors common to different approaches. In the present paper, we provide an overview and discuss some of the existing clinical-theoretical and empirical literature on specific and common factors of PPCA. Several specific and common factors of PPCA were identified. Regarding the former, these included clinical processes (insight; working through; remembering and reconstructing; catharsis, abreaction, and regression; and transference and countertransference) and therapeutic techniques (interpretation of transference, countertransference, dreams, defense mechanisms, and resistance; verbalization; mirroring; and free play). Regarding the latter, these included relational factors (therapeutic alliance and interaction structures), patient factors (willingness to participate, readiness for change, treatment involvement, and positive expectations and hope), therapist factors (interpersonal skills, direct influence skills, credibility, involving parents, playing ability, flexibility, and allegiance), parent and interpersonal environment factors (parental willingness to participate, treatment involvement, treatment expectations, and perceived barriers to treatment participation and therapeutic change; family dynamics; parent-therapist alliance; and social support), mentalizing (of the therapist, client, and parents), and play (symbolization, affect regulation, mental state talk, and patterns of interaction). PPCA appears to work through both specific and common factors, more likely through their synergic interaction. However, empirical support for these therapeutic factors and their mutual interaction remains sparse. Future qualitative and quantitative research should address more in detail the extent to which specific factors, common factors, or both account for the effectiveness of PPCA. Identifying empirically supported specific and common factors and their possible interaction can inform and improve clinical practice and training.